Television producers - Tunstall, Jeremy (Communication and society (Routledge (Firm)), 1993)
A comprehensive survey of the entire spectrum of television broadcasting, conveying an understanding of the particular atmosphere of seven different programming areas including news, sport, documentaries and game shows.